2017
DOI: 10.1016/j.worlddev.2016.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Welfare Impacts of Index Insurance in the Presence of a Poverty Trap

Abstract: This paper evaluates the welfare impacts of an index-based livestock insurance designed to compensate for satellite-based predicted livestock mortality in northern Kenya, where previous work has established the presence of poverty traps. We simulate household wealth dynamics based on rich panel and experimental data. The bifurcated livestock dynamics associated with the poverty trap gives rise to insurance valuation that is highly nonlinear in herd size. Estimated willingness to pay among vulnerable groups who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 24 publications
1
44
1
Order By: Relevance
“…Sources: IBLI: Bageant and Barrett (2017), Chantarat et al (2017), Dror et al (2015), Jensen et al (2015). ACRE: Goslinga (2012), Wills et al (2015), IIF (2017).…”
Section: Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sources: IBLI: Bageant and Barrett (2017), Chantarat et al (2017), Dror et al (2015), Jensen et al (2015). ACRE: Goslinga (2012), Wills et al (2015), IIF (2017).…”
Section: Representationmentioning
confidence: 99%
“…Less attention has been paid to how farmers' access to index insurance interfaces with inequalities already present in farming populations, or of the differential social impact of index insurance schemes upon an already heterogeneous rural population. Studies exploring socioeconomic and welfare issues include Bageant and Barrett (2017), Chantarat, Mude, Barrett, and Turvey (2017), Janzen and Carter (2013), Jensen, Barrett, and Mude (2015), Jensen, Mude, and Barrett (2018), Jensen and Barrett (2017), Peterson and Osgood (2016) and Taylor (2016). While studies increasingly explore socioeconomic dynamics, including those related to inequality and unequal power relations, debate on index insurance and social equity per se is limited, although research is starting to highlight the need for more attention to be directed towards equity dimensions (Müller, Johnson, & Kreuer, 2017;Reeves, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A SECTION SECTION 97 21 The ultra-poverty rate is based on a national rural poverty line equivalent to US$0.5/day. 22 These results are parallel to findings in Chantarat et al (2014) and Barrett et al (2012). 23 For further discussion of Kenya's experience with agricultural insurance, see GoK (2014a), which is the source of the information presented in this section.…”
mentioning
confidence: 62%
“…Barrett et al 2007), and some successes reported (e.g. Chantarat et al 2017), the Binswanger-Mkhize critique should not be treated lightly.…”
Section: − = −mentioning
confidence: 98%